Theoretical Prediction and Analysis of the UV/Visible Absorption and Emission Spectra of Chiral Carbon Nanorings - Rathawat Daengngern (2018)
© 2018 American Chemical Society. UV/vis absorption and emission spectra of recently synthesized chiral carbon nanorings were simulated using first-principles-based molecular dynamics and time-dependent density functional theory (TD-DFT). The chiral carbon nanorings are derivatives of the [n]cycloparaphenylene ([n]CPP) macrocycles, containing an acene unit such as naphthalene, ([n]CPPN), anthracene ([n]CPPA), and tetracene ([n]CPPT), in addition to n paraphenylene units. In order to study the effect of increasing molecular size on absorption and emission spectra, we investigated the cases where n = 6 and 8. Frontier molecular orbital analysis was carried out to give insight into the degree of excitation delocalization and its relationship to the predicted absorption spectra. The lowest excited singlet state S1corresponds to a HOMO-LUMO π-π∗ transition, which is allowed in all chiral carbon nanorings due to lack of molecular symmetry, in contrast to the forbidden HOMO-LUMO transition in the symmetric [n]CPP molecules. The S1absorption peak exhibits a blue-shift with increasing number of paraphenylene units in particular for [n]CPPN and [n]CPPA and less so in the case of [n]CPPT. In the case of CPPN and CPPA, the transition density is mainly localized over a semicircle of the macrocycle with the acene unit in its center but is strongly localized on the tetracene unit in the case of CPPT. Molecular dynamics simulations performed on the excited state potential energy surfaces reveal red-shifted emission of these chiral carbon nanorings when the size of the π-conjugated acene units is increased, although the characteristic [n]CPP blue-shift with increasing paraphenylene unit number n remains apparent. The anomalous emission blue-shift is caused by the excited state bending and torsional motions that stabilize the π HOMO and destabilize the π∗ LUMO, resulting in an increasing HOMO-LUMO gap.